James Baldwin’s ‘If Beale Street Could Talk’, a testimony of Love, Support and Hope amidst the turmoil of Racial Injustice (International Journal of Food and Nutritional Sciences, 2022)
James Baldwin as an author brought a revolution in American literature. Through his works Baldwin portrayed the plight of the Blacks in the unjust White American Society. Moreover, he became the voice of the Blacks and also put forth the personal, social,psychological and emotional trauma of the blacks, gay and bisexual men. ‘If Beale Street Could Talk’, published in 1974 brings out the importance of familial love and support in the time of crisis. Baldwin made an attempt to present this novel from women’s perspective, portraying Tish, the protagonist as his first female narrator.The novel is adapted into a movie by Barry Jenkins, by the same name and was released in the year 2018.The film opens with a quote from Baldwin’s text:Every black person born in America was born on Beale Street, born in the black neighbourhood of some American city, whether in Jackson, Mississippi, or in Harlem, New York. Beale Street is our legacy.In If Beale Street Could Talk, Baldwin writes a novel from a woman’s perspective for the first time, making Tish his first female narrator.